Chopin's Alston and Alston's Chopin. (May 2020) - Jordan, Stephanie
Abstract : This article presents Richard Alston's re-visioning of Chopin's music through two works: Such Longing (in two versions, 2005/2015), and Mazur (2015). Alston rescues the composer from dance associations with romance and sweet sentiment and celebrates his more robust, bolder and darker gamut of expression. The article includes detailed analysis of a range of solos and duets (for two men as well as for a woman and a man). Alston is widely regarded as an exceptionally musical choreographer, and the article identifies a particular choreomusical style emerging from his work. There is discussion of structural aspects, involving both music and dance, pursuing the dynamic interaction between them, and of creative processes and changes in the dances through the history of their performance. A landmark feature of Alston's choreomusical style is to allow rhythmic detail to shift more than most other choreographers would wish, encouraging subtle changes of relation to musical beat and bar-line as movement phrases 'breathe' within performance. I also foreground my own analytical process, which draws from music theory as well as dance principles. Film clips and music examples, some of which incorporate aligned notes on the choreography, illustrate my analyses.